DIVIDEND PERFORMANCE OF DAIRY COMPANIES OVER 2015 TO 2024 - Asli, Ani Asmaa; Azmin, Nur Azwani Mohamad; Azhar, Nurul Badzlin; Mazlan, Siti Nur Aisyah; Wan Mustafa, Wan Nur Maizalieza (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
This research focuses on the factors that influence the dividend performance of dairy companies which are affected by increasing production cost, economic instability and post-COVID-19 conditions that impact the ability of companies to pay stable dividends. The aims of this research are to investigate the relationship between firm-specific financial variable and dividend policy for Malaysian and global dairy firm from 2015 to 2024. A quantitative method is used in this research and secondary sources in the panel data regression analysis to test the impact of profitability, firm size and leverage on the dividend payout ratio. The findings indicate that profitability and firm size are positively associated with dividend payments whereas leverage is negatively associated with dividend payments which means that companies with high leverage are likely to retain their earning instead of paying dividends. In conclusion, the findings of the study emphasize the significance of financial variable in determining the dividend policy in the dairy sector and help investors, manager and policymaker understand the importance of financial variables in assessing in the performance of companies and the stability of dividends in the dairy sector.